Prematuridade tardia: morbidade e fatores maternos e gestacionais associados - Paes, Liliana Soares Nogueira (2018)
Late preterms, born between 340/7 and 366/7 weeks, correspond to 70% of preterm infants in tertiary maternities, have anthropometry similar to full term neonates, but different morbidity and mortality, with an impact on the health of the individual, on the well-being of the family and effects that can last for a lifetime. Objective: to analyze the morbidity of late preterm infants in tertiary maternity, to describe the profile of late preterm infants, to compare the morbidity of late preterm infants with term infants and to each other, to evaluate the mortality of late preterm infants, to identify the maternal and gestational factors associated with late prematurity and to develop a set of strategies for the care of premature infants. METHODS: a hospital-based retrospective cohort with a nested control case performed in a medium-complexity tertiary public maternity hospital, a reference in the state of Ceará, from March 1 to July 15, 2017. 204 neonates with gestational age were evaluated between 340/7 and 366/7 weeks and 205 between 390/7 and 406/7 weeks. Data were analyzed using statistical software SPSS 22.0 and R 3.3.1. Results: Late preterm infants presented higher rates of hypothermia (24.5%), hypoglycemia (30.4%), respiratory distress, both transient taquypnea (28.4%) and RDS (2.5%), jaundice requiring phototherapy (67.6%), use of nasal CPAP (8.8%) and mechanical ventilation (3.4%), early infection (10.3%) and difficulty in breastfeeding (49%). They were more frequently admitted to conventional and intensive care units. They had longer hospitalization time, 6.9 days versus 3.7 days. Maternal factors associated with late-onset prematurity were: maternal age ≥ 35 years, schooling ≥ 12 years, hypertensive disorders, diabetes and, especially, premature rupture of the ovary membranes ≥ 18 hours, with a chance of 16.9. There were three deaths among late preterm infants. Conclusion: there was higher morbidity and mortality of late preterm infants compared to full term infants. There is a relationship between late prematurity and maternal aging and prenatal inadequacy, as well as maternal pathologies such as hypertensive disorders, diabetes and premature rupture of the ovary membranes. A set of strategies of attendance to this population was elaborated.